Pengaruh Penambahan PVP Pada Indikator Alami Curcuma Longa L. Untuk Mendeteksi Boraks Pada Bakso - Neneng Bisyaroh (Tinctura, 2019)
Borax is widely used in making various foods such as meatballs, wet noodles, pisang molen, lemper, siomay, lontong, ketupat , and pangsit. Curcumin contained in turmeric can detect the presence of borax content in meatballs by breaking down the borax bonds to boric acid and binding them to rosa color complex compounds called boron compounds cyano curcumin complex. Making a test strip by immobilizing filter paper on the turmeric indicator which has been added polyvinyl pyrrolidone 1% and applied to the meatballs so that it can determine whether there is a borax content in the meatballs. The response time of the test strip is 30 seconds. The test strips of turmeric extract without the addition of polyvinyl pyrrolidone leave the remaining turmeric color in the meatballs while the test strip results of turmeric extract with the addition of polyvinyl pyrrolidone 1% do not leave the remaining turmeric color in the meatballs. The three meatball samples taken in the Pondok Sukorejo area did not contain borax. Keywords: Borax Content In Meatballs, Strip Test, Turmeric Indicator. ABSTRAK Boraks banyak digunakan dalam pembuatan berbagai makanan seperti bakso, mie basah, pisang molen, lemper, siomay, lontong, ketupat, dan pangsit. Kurkumin yang dikandung oleh kunyit dapat mendeteksi adanya kandungan boraks pada bakso dengan menguraikan ikatan–ikatan boraks menjadi asam borat dan mengikatnya menjadi senyawa kompleks warna rosa yang disebut dengan senyawa boron cyano kurkumin kompleks. Pembuatan strip test dengan cara mengimobilisasikan kertas saring pada indikator kunyit yang telah ditambah polivinil pirolidon 1% dan diaplikasikan pada bakso sehingga dapat mengetahui ada tidaknya kandungan boraks dalam bakso tersebut. Waktu respon dari strip test yaitu 30 detik. Strip test dari ekstrak kunyit tanpa penambahan polivinil pirolidon meninggalkan sisa warna kunyit pada bakso sedangkan hasil strip test dari ekstrak kunyit dengan penambahan polivinil pirolidon 1% tidak meninggalkan sisa warna kunyit pada bakso. Ketiga sampel bakso yang diambil di wilayah Pondok Sukorejo tidak mengandung boraks. Kata kunci : Kandungan Boraks dalam Bakso, Strip Test, Indikator Kunyit